INCIDENCE OF A BUDGET IN OCCUPATIONAL SAFETY AND HEALTH IN THE COSTS AND EXPENSES - Flores Pariona, Cecilia Flores Pariona Mirtha (2016)
This article addresses those disbursements in occupational health and safety that should be considered as an investment facing all those costs and expenses that can be triggered, as a result of an accident or occupational illness. An accident results in costs for the direct labor of the injured person, the partner who employs his time to assist him, the replacement personnel, the cost of the supervisor’s indirect labor and expenses such as compensation for the accident, medical expenses, hospitalization, fines, repair of machinery and others. These generate losses for the company and can even affect the productivity of the worker, due to the paralyzes caused by the accidents. Employers have a moral and legal responsibility. There is a law on health and safety at work, nevertheless not always everyone is able to follow it, although it is true that this law does not mention the use of a budget, it is essential to have this management tool and investments that are made as provision of personal protection equipment, safety training, health coverage, among others. For this, there must be a commitment of both employer and worker, they all must generate a preventive culture.